Heat Roadmap Europe: Spatial assessment of district heating potential for strategic planning in Europe - Georgati, Marina; Nielsen, Steffen; Moreno, Diana; Mathiesen, Brian Vad (International Journal of Sustainable Energy Planning and Management, 2026)
Heating is one of Europe’s most energy-intensive sectors. District heating (DH) offers a key pathway to decarbonisation by integrating renewable energy (RE) and excess heat (EH) and reducing fossil fuel dependency. However, as heat demand and supply vary geographically, planning DH expansion requires understanding the spatial variability of heat demand, resources and cost-effectiveness of the systems. This study presents a geospatial analysis of DH potential, combining RE/EH resources and investment costs to model the distribution and economic feasibility of DH systems. Key contributions include a harmonised assessment of DH potential across European Union countries, a prioritisation framework that identifies the most cost-effective locations for DH, and an analysis of regional differences in heat market share. These insights are supported by high-resolution mapping that highlights strategic priority regions at the NUTS 2 level. The study also improves the accuracy of the Pan-European Heat Atlas, making it available as an open-access dataset and tool. The results identify regional variations in DH potential and RE/EH availability, highlighting local opportunities for efficient deployment. These findings support policymakers, regional planners and researchers in designing strategies to accelerate DH deployment toward a 55% DH market share across Europe.